👤

solve by completing the square.
1. x²-2x-3=0
2. 8x+10=-2x²​


Sagot :

Step-by-step explanation:

[tex] {x}^{2} - 2x - 3 = 0 \\ step1 \\ add + 3 \: both \: side \\ {x}^{2} - 2x - 3 + 3 = 0 + 3 \\ {x}^{2} - 2x = 3 \\ step2 \\ take \: half \: of \: 2 \\ half \: of \: 2 \: is \: 1 \\ take \: square \: of \: 1and \: then \\ add \: both \: side \\ {x}^{2} - 2x + {1}^{2} = 3 + {1}^{2} \\ {(x -1)}^{2} = 4 \\ \sqrt{ {(x - 1)}^{2} } = \sqrt{4} \\ (x - 1) = + and - 2 \\ x - 1 = 2 \: and \: x - 1 = - 2 \\ x - 1 + 1 = 2 + 1 \: and \: x - 1 + 1 = - 2 + 1 \\ \\ x = 3 \: and \: x = - 1 \\ s.s = {3 \: and \: - 1}[/tex]